2022
DOI: 10.1177/03611981221101896
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Approach to Healthy Airport Terminal Buildings: Spatial-Temporal Analysis of Mitigation Strategies for Addressing the Pollutants that Affect Climate Change and Human Health

Abstract: The potential environmental and human health impacts associated with constructing and operating terminal buildings is explored for commercial airports in the United States. Research objectives are to quantify: (1) baseline and mitigated greenhouse gas (GHG) and criteria air pollutant (CAP) emissions; (2) operational costs; and (3) climate change damages from terminal building construction and materials, operational energy consumption, water consumption and wastewater generation, and solid waste generation. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Greer et al focused on the impact of terminal renovation and maintenance on climate change and human health by analyzing the baseline and mitigated GHG and CAP emissions associated with building and operating terminals. They quantified life cycle GHG and CAP emissions, operational costs, and monetized climate damages for four modules, namely, building materials; operational energy; water and wastewater; and solid waste and showed that the electricity mix, amount of electricity consumed in the terminal, terminal gross area, and amount of compostable in the solid waste stream have the most impact on increasing annual Global Warming Potential (GWP) (Greer et al, 2023).…”
Section: Findings and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Greer et al focused on the impact of terminal renovation and maintenance on climate change and human health by analyzing the baseline and mitigated GHG and CAP emissions associated with building and operating terminals. They quantified life cycle GHG and CAP emissions, operational costs, and monetized climate damages for four modules, namely, building materials; operational energy; water and wastewater; and solid waste and showed that the electricity mix, amount of electricity consumed in the terminal, terminal gross area, and amount of compostable in the solid waste stream have the most impact on increasing annual Global Warming Potential (GWP) (Greer et al, 2023).…”
Section: Findings and Resultsmentioning
confidence: 99%
“…Altuntas et al applied gate-to-gate method of LCA in the analysis of ground operations of APU and GPU in airports but did not include GSE in the analysis (Altuntas et al, 2014). Another study focused only on the LCA of airport terminal buildings to analyze the mitigation strategies and address the pollutants that affect climate change and human health (Greer et al, 2023). Similar research centered on the LCA of GHG emissions and economic implications of electrifying gate operations (Greer et al, 2021).…”
Section: Knowledge Gaps In Existing Literaturementioning
confidence: 99%
See 3 more Smart Citations